Odpowiedzi

2010-01-20T17:59:52+01:00
A)=-(3-2)+3= -1 + 3 = 2
b)=-15+(-4+7)-)-8-11= -15+3+8-11= -15
c)=28-39-14+12-81=-94
d)=37-18-48-9=-38
2010-01-20T18:00:41+01:00
A) -(-(-3)+(-2))+(-(-3))
-(3-2)+3
-(1)+3
2
b) -15+(-4-(-7))-)-8)+(-11) <--tu wpisalane jest przed 8 w zla strone nawias
-15+(-4+7)+8-11
-15+3+8-11= -15
c)28-39+(-14)-(-12)-81
28-39-14+12-81= -94
d)37+(-18)-(-(-48))+(-9)
37-18-48-9= -38
Najlepsza Odpowiedź!
2010-01-20T18:05:18+01:00
-(-(-3)+(-2))+(-(-3))=
-(3-2)+(3)= -3+2+3=2

-15+(-4-(-7))-)-8)+(-11)=
-15+(-4+7+8)-11=
-15-4+7+8-11=-15

28-39+(-14)-(-12)-81=
28-39-14+12-81=-94

37+(-18)-(-(-48))+(-9)=
37-18+(48)-9= 37-18+48-9= -38